Preoperative testing and medical therapy intervention to improve perioperative outcomes in noncardiac surgical patients. - Alphonsus, Christella (Department of Anaesthesia and Perioperative Medicine, 2023)
Introduction: Cardiovascular disease is the leading cause of death worldwide and a growing concern in low-and-middle income countries, including those in Africa. Patients with cardiovascular disease often have poorly managed chronic conditions in the African setting, which impacts their outcome when they present for non-cardiac surgery. This cohort has an increased risk of perioperative cardiovascular complications. This series of studies explored evidence-based perioperative cardiovascular management strategies in patients with high-risk cardiac comorbidities presenting for non-cardiac surgery. Methods: This was achieved through five objectives which formed five separate but interconnected research studies. The first objective was to study the approach of natriuretic peptide-directed medical therapy in non-surgical patients to inform development of a preoperative protocol in surgical patients through a systematic review. The second objective was to conduct systematic review on exercise therapy in nonsurgical patients to inform development of a preoperative protocol in surgical patients. The third objective was to define the population who would need optimisation before surgery in the Western Cape, South Africa through a prospective observational study of risk stratification. The fourth objective was to explore the broader applicability of perioperative cardiovascular management of high-risk patients by examining cardiovascular outcomes after surgery on the African continent (a sub-study of a larger African cohort study). The fifth objective was to produce national guidelines on cardiovascular risk stratification in a South African and African surgical population. Main results: The systematic reviews showed potential utility for exercise therapy in the optimisation of cardiac patients for non-cardiac surgery. Medical therapy optimisation guided by natriuretic peptide testing did not demonstrate a consistent reduction in natriuretic peptides, but did support a potential mortality benefit in non-surgical patients. The cohort of cardiac patients presenting for non-cardiac surgery in the Western Cape carries significant cardiac risk and needs perioperative cardiovascular management. This was confirmed by the rate of adverse cardiovascular outcomes reported on the African continent. These data supported the development of context-specific national cardiovascular risk stratification guidelines. Conclusion: The cardiovascular burden and risk for perioperative cardiovascular complications presents a challenge in low- and middle-income countries like South Africa, and more broadly Africa. This is a growing phenomenon which needs the collaborative effort of perioperative physicians and the implementation of evidence-based strategies in perioperative cardiovascular management.